Fatigue Strength Analysis of Cracked Wind Turbine Planetary Gear Train Under Variable Load Excitation - Ben Chen; Shijing Wu; Pan Zheng; Jun Wang; Qiang Chen; Sujie Gao; Jianhua Zhou (Jixie chuandong)
The external excitation caused by random wind load can greatly affect the fatigue life of the wind power transmission system. A four-component model considering the wake effect is used to simulate the random wind speed of a wind farm， and combined with the finite element method， the fatigue life of the wind power planetary gear train is obtained. On this basis， the influence of the depth， length and extension angle of the sun gear single-tooth and double-tooth root cracks on the fatigue strength of wind power planetary gear trains is studied based on the sub-model method. Finally， it is found that the influence degree of the crack size parameters on the fatigue life of the wind power planetary gear train is: crack depth> crack length> crack extension angle. The effect of double root cracks on fatigue life is much greater than that of single root cracks， the fatigue life of the first-engaged tooth in the double-root crack state is much shorter than that of the single-root crack state， and the fatigue life of the later-engaged tooth is slightly larger than that of a single-tooth root crack state. Related research provides a theoretical basis for optimizing the service performance of wind turbines.